Ovalbumin and Kappa-Carrageenan Mixture Suppresses the Oxidative and Structural Changes in the Myofibrillar Proteins of Grass Carp (Ctenopharyngodon idella) during Frozen Storage - Noman Walayat; Xiukang Wang; Asad Nawaz; Zhongli Zhang; Abdullah; Ibrahim Khalifa; Muhammad Hamzah Saleem; Bilal Sajid Mushtaq; Mirian Pateiro; José M. Lorenzo; Sajid Fiaz; Shafaqat Ali (MDPI AG, 2021)
This study was done to analyze the cryoprotective influence of ovalbumin (OVA) with kappa-carrageenan (KC) in grass carp myofibrillar proteins during frozen storage. Ca2+-ATPase activity of MP was significantly reduced due to protein denaturation and showed a direct association with decreased sulphydryl (SH) contents and tertiary structural properties. Besides that, an increase in carbonyl, surface hydrophobicity, and dityrosine contents was observed. The addition of OVA-KC significantly restricted the decline in Ca2+-ATPase and SH groups, which were further confirmed by the retarded increase in carbonyls. Furthermore, the addition of OVA-KC increased the stability of α-helix contents. Moreover, MP treated with 6% OVA-KC also improved intermolecular interaction forces linked with gelling and water holding properties of MP. Therefore, it can be concluded that OVA-KC could be used as an effective cryoprotectant in fish and related products for preservation and commercialization.